A Case-Control Study of the Association Between GSTP1 Gene Polymorphisms (rs1695 and rs1138272) and the Susceptibility to Male Infertility in the Moroccan Population - Harmak, Houda; Redouane, Salaheddine; Charoute, Hicham; Aniq Filali, Ouafaa; Barakat, Abdelhamid; Rouba, Hassan (Genetic testing and molecular biomarkers, 2025)
Infertility affects 10-15% of couples worldwide, with male factors accounting for half of cases. Environmental, behavioral, and genetic problems contribute to spermatogenic failure in 30% of idiopathic male infertility cases. Other factors, such as oxidative stress (OS), cause impaired spermatogenesis, abnormal sperm morphology, and reduced motility, eventually triggering male infertility. In the male reproductive tract, glutathione -transferase (GST) family antioxidants are essential for preventing OS, detoxification, and DNA damage protection. GSTP1 isoenzyme, one of GST members, has previously been linked to male infertility, and this case-control study is the first to assess the possible association of GSTP1 gene polymorphisms (rs1695 and rs1138272) with nonobstructive azoospermia and severe oligospermia within 300 patients and 300 controls from the Moroccan population using an allele-specific PCR. The statistical analysis was performed with the R programming language. Genotyping of polymorphisms fitted the Hardy-Weinberg equilibrium in both cases and controls ( > 0.05), but no significant association was found in rs1695 (odds ratio [OR] = 1.238, 95% confidence interval [CI] = 0.855 to 1.794, = 0.258, power = 0.204) and in rs1138272 (OR = 1.192, 95% CI = 0.852 to 0.1668, = 0.304, power = 0.176). Likewise, results from haplotype analysis (OR = 1.25, 95% CI = 0.61 to 2.57, = 0.537) and SNP-SNP interactions (OR = 1.522, 95% CI = 0.838 to 2.762, = 0.166) demonstrated no correlation with the risk of male infertility. The two SNPs (rs1695 and rs1138272) of the gene loci are not associated with male infertility susceptibility in Moroccan subjects. Yet, future investigations with a larger sample size may conclusively help to confirm this association.